Technologies used in the context of violence against women: an integrative review - da Silva Santos , Rosângela; Vitória Marinho Portela , Maria; Francisco do Nascimento , Beatriz; Cláudia Mateus Barreto , Ana (Seven Editora, 2023)
Objective: to identify the scientific publications about technologies related to violence against women published from 2011 to 2021.  Method: an integrative literature review. Guiding question: "What technologies related to violence against women were published in the period from 2011 to 2021?". Database: Virtual Health Library. Keywords: violence against women AND technology; information technology AND violence against women. Inclusion criteria: full texts, available in the languages Portuguese and English, and Spanish, published between the years 2011 to 2021. Exclusion criteria: duplicate publications; paid publications; Theses; master's dissertations; course completion work; productions not related to the objective of the study. Results:  27 articles were identified, of which 8 were selected: 5 from LILACS and 3 from MEDLINE.  Conclusion: the study met the objective of identifying scientific productions about technologies related to violence against women. It identified several positive and negative aspects regarding the use of technology in the fight against violence against women. It is recommended to conduct studies that address the technologies and how they can influence the fight against this violence during the quarantine period for COVID-19.DOI: https://doi.org/10.56238/devopinterscie-116